A scientifically validated combination of garcinol, curcuminoids, and piperine for mild to moderate nonalcoholic steatohepatitis patients—results from a randomized, double-blind, placebo-controlled study - Majeed, Muhammed; Nagabhushanam, Kalyanam; Noureddin, Mazen; Paulose, Shaji; Barik, Chinmoy; Saklecha, Santosh; Mundkur, Lakshmi (Frontiers in Nutrition, 2023)
Background: Garcinol is a naturally occurring compound from fruit rind of the Garcinia indica, with antioxidant, anti-inflammatory, and anticancer properties. Curcuminoids are the active molecule from the rhizome of Curcuma longa, studied extensively for its health benefits as an anti-inflammatory and antioxidant activities. Non-alcoholic steatohepatitis (NASH) is the progressive form of nonalcoholic steatohepatitis characterized by liver fat and inflammation. Objective: To evaluate the clinical efficacy and safety of Garcinol, Curcuminoids and piperine (GCP) combination in patients with mild to moderate NASH in a randomized, double-blind, placebocontrolled study. Methods: The patients received one tablet (450mg) of GCP containing garcinol-50 mg, curcuminoids -250 mg and piperine 5mg or a placebo (450 mg of microcrystalline cellulose) twice daily for 90 days. Changes in circulating aspartate aminotransferase (AST), alanine transaminase (ALT) levels, liver stiffness measurement (LSM), and controlled attenuation parameter (CAP) using Fibroscan were compared from baseline to day 90. Anthropometric parameters, serum levels of lipids, Interleukin (IL-6), hsCRP, and adiponectin were estimated. Safety was evaluated by laboratory parameters and by monitoring adverse events. Results: Seventy-two patients were randomized and 63 (GCP=32, Placebo =31) completed the study. The mean age of the patients was 48.3 ± 8.7 years (36 males and 27 females). The mean reduction in AST (U/L) was 9.53 in GCP and 3.16 in placebo (P<0.001) and that of ALT(U/L) was 13.47 in GCP and 7.43 in Placebo (P=0.002). The liver stiffness and CAP scores showed a better reduction in GCP (0.56 kPa and 12.38 db/m) compared to placebo (0.064 kPa and 10.42 db/m) p<0.05. Consequently, the noninvasive Fibroscan-AST (FAST) score reduction was also found to be significant in GCP compared to placebo. Additionally, body weight, lipid levels, hsCRP, and IL-6 in serum decreased, while adiponectin levels increased in GCP-supplemented participants compared to placebo. The combination of garcinol and curcuminoids was well tolerated with no significant changes in hematological and clinical laboratory parameters during the 90-day supplementation. Conclusion: Our results suggest that GCP could be a possible supplement for the management of NASH.The trial was registered prospectively with the Clinical Trial Registry of India (CTRI) with the registration number CTRI/2019/11/022147.